The potential of coconut shells through pyrolysis technology in nigeria - Ahmad, R.K. (Springer Science and Business Media Deutschland GmbH, 2021)
The outer hard shell that encloses the coconut fruit is known as the coconut shell. It is available in plentiful quantities and utilizes as an energy source throughout the tropical countries worldwide. The current world production of coconut fruits and the availability of its biomass wastes have the potential to generate power for low emissions in different applications. Coconut shells are among the untapped energy source from agricultural residues. Rural small-scale farmers in Nigeria are not familiar with the technological process of utilizing the coconut shells for sustainable biofuel production. Usually, they use the shells for open burning charcoal production and as organic fertilizer. Future sustainable and eco-friendly thermochemical technology like pyrolysis produces the entire three biofuels products (solid, liquid, and gas) based on the biomass type and its availability. The products are in the form of charcoal/biochar, bio-oil, and biogas fuels used as a substitute for fossil fuels. This chapter highlights the potentials of utilizing the coconut shells by the thermochemical conversion method, specifically the pyrolysis method. The major contribution it will generate to the economic and industrial development of the country. Industries have the potentials in contributing to this sector when biomass wastes are utilized as raw materials in industrial applications. The use of biofuel obtained from biomass thermochemical conversion has more advantages over the use of raw biomass, in terms of clean energy and environmental sustainability concerns. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.